2018
DOI: 10.1590/0100-29452018874
|View full text |Cite|
|
Sign up to set email alerts
|

Microencapsulation of pequi pulp oil by complex coacervation

Abstract: Pequi pulp oil, Caryocar brasiliense, is rich in carotenoids, antioxidant compound easily oxidized by the presence of heat, light and oxygen. In order to improve its stability, pequi oil was microencapsulated by complex coacervation using gelatin and Arabic gum as encapsulating agents. Twenty formulations were prepared using a 23 central composite rotational design. The influence of temperature, stirring velocity and core material in the oil coacervation were evaluated, aiming to preserve carotenoids present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Values higher than those found in the present study, these differences can be attributed to the molecular interaction of AG with MOPN during the emulsion, making it necessary to study improvements in the process conditions to increase the efficiency of the interaction between the polysaccharides, such as a longer time of emulsion, which may favor an increase in encapsulation yield and efficiency. ther studies with Brazilian cerrado fruit oils using AG associated with gelatin as a wall material obtained a yield of 96.45% and an efficiency of 96.68% in the complex coacervation of pequi oil (Justi, Sanjinez-Argandoña, & Macedo, 2018); and 82.55 and 70.72% of yield and efficiency, respectively, for bacuri oil (Lima et al, 2019). These studies suggest that the results obtained in the present work are considered effective, since the efficiency is within the values obtained by these authors.…”
Section: Microencapsulation's Yield and Efficiencysupporting
confidence: 86%
See 1 more Smart Citation
“…Values higher than those found in the present study, these differences can be attributed to the molecular interaction of AG with MOPN during the emulsion, making it necessary to study improvements in the process conditions to increase the efficiency of the interaction between the polysaccharides, such as a longer time of emulsion, which may favor an increase in encapsulation yield and efficiency. ther studies with Brazilian cerrado fruit oils using AG associated with gelatin as a wall material obtained a yield of 96.45% and an efficiency of 96.68% in the complex coacervation of pequi oil (Justi, Sanjinez-Argandoña, & Macedo, 2018); and 82.55 and 70.72% of yield and efficiency, respectively, for bacuri oil (Lima et al, 2019). These studies suggest that the results obtained in the present work are considered effective, since the efficiency is within the values obtained by these authors.…”
Section: Microencapsulation's Yield and Efficiencysupporting
confidence: 86%
“…The conservation of carotenoids presents in oils extracted from brazilian cerrado fruits and microencapsulated by complex coacervation was also verified by other authors. Justi et al (2018), in pequi oil microcapsules, obtained total carotenoid ranging from 60.30 to 192.04 μg g -1 . France et al (2019), in the analysis of macauba oil, obtained 267.37 ± 3.09 mg of β-carotene 100 g -1 of oil.…”
Section: Chlorophyll and β-Carotenementioning
confidence: 99%
“…Lemos et al ( 56 ) investigated the influence of hydrodynamic conditions in the buriti oil coacervation, rich in carotenoids, using gelatin/alginate as matrix and identified the agitation speed as having a strong influence on the microcapsule size. Justi et al ( 61 ) studied the pequi oil microencapsulation using gelatin and gum arabic as encapsulating matrices in order to improve the oil stability. In that study, the influence of temperature, agitation speed and core material on oil coacervation was evaluated in the preservation of carotenoids present in the oil.…”
Section: Microencapsulation Methods For Vegetable Oilmentioning
confidence: 99%
“…One way to protect the functional and nutraceutical properties of an unstable substance is to use microencapsulation with biobased polymers. Indeed, some studies have been reported on encapsulation of pequi oil (Alexandre et al, 2019;Comunian et al, 2020;Justi et al, 2018;Oliveira et al, 2018) using polymeric encapsulants such as gelatin and gum Arabic (Justi et al, 2018), cashew gum and gelatin (Alexandre et al, 2019), whey protein isolate (Comunian et al, 2020), and whey protein isolate, maltodextrin, and inulin (Oliveira et al, 2018). Ionic gelation is an efficient and known encapsulation technique performed under room temperature and pressure (Menin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%